The restoration work of Jan de Meijer and A.A. Kok (Bulletin KNOB, 2005)
This article is a brief review of the restoration work of the architects Jan de Meijer and Antoon Abel Kok. Both architects worked in Amsterdam in the first half of the twentieth century. De Meijer and Kok each worked in their own way without adhering to the established restoration theories of the so called ‘Basic Principles’, published in 1917.Jan de Meijer mainly reconstructed early seventeenth-century Renaissance buildings which, according to him, had been mutilated by later refurbishments. The premises Oudezijds Voorburgwal 249 and 14 and Nieuwezijds Voorburgwal 75 are examples of this. With his reconstructions he restored these buildings to an ideal seventeenth-century state. In his view the cross-bar windows and the proportions of these Renaissance buildings were the perfect expression of professional skill.Nevertheless De Meijer did not exclusively restore buildings to their original state. Singel 440 and Brouwersgracht 48 show that he, too, sometimes only executed repairs and practical alterations. De Meijer thought that the restoration question was too complicated to be solved by means of dogmas. It was important to him to ask himself the question what should be the approach to each individual restoration.His views on the traditional building methods, the idealisation of Renaissance buildings and the use of the cross-bow window saw to it that he did not adhere to the established restoration theories, but went his own way entirely. A.A. Kok also restored in his own individual way. Sometimes he only repaired, as in the case of Prinsengracht 2, and appeared to adhere completely to the Basic Principles and theories of Ruskin.In other cases, as in Kattegat 4-6, he restored the premises to their original state, abandoning the Basic Principles. Kok was a man with practical know-how; consequently, he looked at each building separately and for each building his point of view on the restoration in question was different. He preferred to take up a position halfway between the views on restoration of Ruskin and Viollet-le-Duc.If it was necessary to demolish part of a building and rebuild it, he carried this out as much as possible with old materials, so as to approach the original state as closely as possible. It was not just the beauty of the individual building that was important to Kok, but also the beauty of the city of Amsterdam. His restoration work should therefore be viewed in connection with the restoration of the city as a whole.A good building only needed repairs, a bad building had to be renewed and improved. So both architects did not adhere to fixed theories and dogmas, but considered each building separately. Kok and De Meijer show a restoration practice that was quite different from the restoration theories at the time. From a review of their work it appears that the restoration practice in the early twentieth century was more complicated as has long been assumed.